The Influence of Communication Strategy on User Satisfaction at the Medan State Polytechnic Library - Dalim, Muhammad (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The title of this research was The Influence of Communication Strategy and Prime Service on Library Members’ Satisfaction at the Library of Politeknik Negeri Medan. The research used the theory of satisfaction. Kotler (2014) points out that there are two theories of satisfaction: theory of performance expectation and theory of cognitive inappropriateness. Theory of performance expectation states that consumer satisfaction is the function of consumers’ expectation of the result. If the result is in accordance with what has been expected, consumers will be satisfied, if it exceeds what has been expected, they will be more satisfied, but if it is not in accordance with what has been expected, they will be dissatisfied. The population was 5,994 members of the library, and 98 of them were used as the samples, taken by using Slovin formula. The data were gathered by using questionnaires and conducting documentation and observation. The result of the research showed that the factors of communication strategy and prime service had positive and significant influence on library members’ satisfaction which indicated that the better the communication strategy and the prime service, the higher the library members’ level of satisfaction.